Amyloidosis cutis dyschromica cases caused by GPNMB mutations with different inheritance patterns. Issue 1 (October 2021) - Qin, Wen; Wang, Huijun; Zhong, Weilong; Bai, Juan; Qiao, Jianjun; Lin, Zhimiao
Highlights: We present nine ACD cases caused by GPNMB mutations, including eight with autosomal-recessive and one with autosomal-dominant pattern. The recurrent mutation c.565C > T (p.R189*) present in six cases originated from founder effect. The autosomal-dominant mutation p.C413S displayed mislocalization and exerted a dominant-negative effect on wild-type GPNMB. Abstract: Background: Amyloidosis cutis dyschromica (ACD) is a rare form of primary cutaneous amyloidosis featured by reticulate dotted hypo- and hyperpigmentation. Recently, loss-of-function mutations in GPNMB, encoding glycoprotein (transmembrane) nonmetastatic melanoma protein B, were found in autosomal-recessive or semi-dominant ACD. Objective: This study aims to detect the genetic defect underlying ACD in nine separate cases and to investigate the functional consequences of the mutants. Methods: Nine ACD cases were collected including eight with autosomal-recessive pattern and one with autosomal-dominant pattern. Whole-exome sequencing or Sanger sequencing of the GPNMB gene was performed to detect the pathogenic mutations. Haplotype analysis was employed to determine the origin of mutation c.565C > T using adjacent highly polymorphic SNPs. Immunoblotting and subcellular localization assessments were performed to evaluate the expression of the mutants using HEK293 cells transfected with the GPNMB constructs. Results: We detected four recurrent mutations (c.393 T > G, p.Y131*; c.565C > T, p.R189*; c.1056delT, p.P353Lfs*20; c.1238 G > C, p.C413S) and two novel mutations (c.935delA, p.N312Tfs*4; c.969 T > A, p.C323*) in GPNMB . Mutation c.565C > T found in six separate ACD cases shared a common haplotype. The two novel mutations caused a decreased abundance of truncated proteins. The c.1238 G > C mutation, which was detected in the autosomal-dominant case, caused abnormal reticular subcellular localization of the protein. A major percentage of wildtype changed its expression pattern when co-expressed with this mutant. Conclusions: Our findings proved that the recurrent mutation c.565C > T originated from a founder effect. The autosomal-dominant ACD associated mutation p.C413S played its pathogenic role through a dominant-negative effect on wild-type GPNMB. This study expands the genotype and inherited modes of ACD and improves our understanding of the pathogenesis of this disorder.